Systems biology of autophagy in leishmanial infection and its diverse role in precision medicine - Guhe, Vrushali; Ingale, Prajakta; Tambekar, Anil; Singh, Shailza (Frontiers in Molecular Biosciences, 2023)
Constraint in treatment available for leishmaniasis, allow researchers to focus on novel target for potential treatment regimen. Autophagy is cynosure in leishmaniasis and emerging as promising therapeutic regimen. In Leishmania and host autophagy is salient, although mechanistic approach is not well deciphered in Leishmania parasite. To the best of our knowledge, we are reporting for the first time autophagy in both the host and the parasite and additionally discussed drugs which are showing anti-leishmanial effect by modulating autophagy. This review is addressing the aspects viz., 1) autophagy: How autophagy proteins are getting targeted for therapeutic studies, 2) lipid metabolism: How lipid metabolism is interconnected with autophagy, 3) microRNAs helping autophagy and lipid metabolism and 4) Systems biology approach to design novel autophagy dependent therapeutics in leishmaniasis by employing AI (artificial intelligence), ML (machine learning) approaches, mathematical modeling, network analysis and other computational tools. For exploration of intricate autophagy pathway, here, we have demonstrated different databases for autophagy and leishmaniasis which pinpoints newer targets. We conclude the paper addressing the potential future perspective in this area, which might provide a more in-depth insight into the dynamics of leishmanial autophagy in collaboration with lipids, miRNA, proteins and essential biomolecules.